Desarrollo de software para digitalización y optimización del proceso de registro de proveedores en el consejo colombiano de seguridad (2024)
As part of its digital transformation process, the Colombian Security Council (CCS) sought to systematize the registration of its suppliers, a critical area for efficiency operational and information security. Currently, this process was carried out manually, which led to delays, errors and lack of data security. For To address these challenges, a comprehensive web application was developed that automated and optimized the supplier registration, using technologies such as PHP, CodeIgniter and Bootstrap. The application offered real-time tracking, efficient data management and performance measures advanced security. This not only improved the operational efficiency of the CCS, but also strengthened its position as a leader in security and risk prevention in Colombia.